2017
DOI: 10.1186/s11671-017-1878-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Charge Density Functional Tight-Binding Study of Poly(3,4-ethylenedioxythiophene): Poly(styrenesulfonate) Ammonia Gas Sensor

Abstract: Geometric and electronic properties of 3,4-ethylenedioxythiophene (EDOT), styrene sulfonate (SS), and EDOT: SS oligomers up to 10 repeating units were studied by the self-consistent charge density functional tight-binding (SCC-DFTB) method. An application of PEDOT:PSS for ammonia (NH3) detection was highlighted and investigated both experimentally and theoretically. The results showed an important role of H-bonds in EDOT:SS oligomers complex conformation. Electrical conductivity of EDOT increased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The SCC-DFTB provided the molecular structures, energies and electronic properties in excellent agreement with DFT methods but was ∼100-1000 times faster. The SCC-DFTB can also include reliable description of dispersions and weak interactions (Van der Waals and H-bonding) that are important roles for investigation of gas adsorption on a sensing material which is consistent with experimental observations [40,45,47,48]. Moreover, the SCC-DFTB was proved to be effective in the simulation studies of boron nitride nanostructures systems [49][50][51].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The SCC-DFTB provided the molecular structures, energies and electronic properties in excellent agreement with DFT methods but was ∼100-1000 times faster. The SCC-DFTB can also include reliable description of dispersions and weak interactions (Van der Waals and H-bonding) that are important roles for investigation of gas adsorption on a sensing material which is consistent with experimental observations [40,45,47,48]. Moreover, the SCC-DFTB was proved to be effective in the simulation studies of boron nitride nanostructures systems [49][50][51].…”
Section: Introductionsupporting
confidence: 72%
“…The SCC-DFTB method is based on a second-order expansion of the DFT total energy expression in term of charge density variation with respect to a reference density [41][42][43][44][45]. The total energy of SCC-DFTB based on the Kohn-Sham orbitals is given by following equation [44]:…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Molecular orbitals and energy values for PEDOT (charge +1) and PSS (charge −1) models are in good agreement with previous works for describing the polaron state. [33,34] The Mulliken charges distribution of the system showed that most of the negative charge (−0.64) in PSS is localized on the sulfonate anion. Then, starting from PEDOT and PSS models, we converged to an optimized PEDOT:PSS model.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This interaction is specically strong because the NH 3 molecules can directly bind to H atoms of PEDOT:PSS via the lone-pair electrons of the N atoms with a binding distance of 2.00Å and the interaction energy of 6.596 kcal mol À1 according to a theoretical study using the selfconsistent charge density functional tight-binding method. 27 As a result of the charge transfer from the adsorbed NH 3 molecules to PEDOT:PSS, the number of holes decreases and the depletion region thickness of the PEDOT:PSS layer increases, leading to the expansion of the neutral polymer backbone region and the increase in the resistance. Thus, the EL intensity of sensor reduces in the presence of NH 3 and recovers to its initial value in the absence of NH 3 molecules.…”
Section: Resultsmentioning
confidence: 99%